2022
DOI: 10.1128/jb.00060-22
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis EspK Has Active but Distinct Roles in the Secretion of EsxA and EspB

Abstract: Mycobacterium tuberculosis uses its ESX-1 system to secrete EsxA and EspB into a host to cause disease. We show that EspK, a protein whose role in the ESX-1 machinery was thought to be nonessential, is needed by M. tuberculosis for optimal EsxA and EspB secretion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 55 publications
2
11
0
Order By: Relevance
“…The processed form of EspB, which corresponds to its N-terminal half, forms heptameric rings ( 33 ). EspK functions to keep EspB from oligomerizing inside of the mycobacterial cell ( 71 ).…”
Section: Discussionmentioning
confidence: 99%
“…The processed form of EspB, which corresponds to its N-terminal half, forms heptameric rings ( 33 ). EspK functions to keep EspB from oligomerizing inside of the mycobacterial cell ( 71 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, since then, multiple studies have shown the presence of EspK in the capsule or culture filtrate ( 38 , 54 , 55 ). Recently ( 39 ), it was shown that EspK is exported by M. tuberculosis to be localized in its cell wall. As EspB oligomerizes upon secretion, it is expected that any control on this event would happen before its secretion.…”
Section: Discussionmentioning
confidence: 99%
“…As EspB oligomerizes upon secretion, it is expected that any control on this event would happen before its secretion. We hypothesize that EspK binds to EspB to prevent a premature oligomerization that could stop its secretion ( 39 ). We have shown that one of the factors that favors EspB oligomerization is cleavage of its C-terminal region, which occurs during secretion within the periplasm, as well as the presence of an acidic environment ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple different pressures may differentially select for variants related to ESX-1 activity. This secretion system influences virulence and antigenicity in MTBC (Garces et al, 2010; Lim et al, 2022) by controlling the secretion of the immunodominant antigens ESAT-6 ( esxA ) and CFP-10 ( esxB ) (Covert et al, 2001; Guinn et al, 2004; Hsu et al, 2003), stimulating the innate immune response and cytokine secretion (Pandey et al, 2009, p. 2; Stanley et al, 2007), and promoting the intracellular growth of the pathogen (Lewis et al, 2003; Stanley et al, 2003). Through modulating the immune response, as well as cellular permeability (Garces et al, 2010), ESX-1 function may also influence antibiotic activity or resistance (Torres Ortiz et al, 2021).…”
Section: Discussionmentioning
confidence: 99%